Outcome of pneumatic retinopexy at a tertiary eye care centre in Nepal - Thapa, R; Shrestha, MK; Gurung, R; Ruit, S; Paudyal, G (Kathmandu University Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: Rhegmatogenous retinal detachment is one of the commonly encountered retinal problems where timely treatment could prevent irreversible vision loss. Pneumatic retinopexy (PR) is a simple and minimally invasive procedure for retinal reattachment. Aim: This study aimed to assess the outcome of pneumatic retinopexy in primary rhegmatogenous retinal detachment at our facility. Study design: This was a retrospective- prospective, interventional case series. Materials and methods: All subjects with rhegmatogenous retinal detachment who underwent pneumatic retinopexy at Tilganga Eye Centre of Nepal from January 2002 to June 2007 were included in this study. Results: A total of 32 cases were included in the study. The mean age of patients was 55.2 year (SD=11.0). The majority of cases (62.5%) presented within two weeks of symptoms with blurring of vision in 90% of cases. Pre-operatively, 56.3% (18) patients had a best corrected distance visual acuity of < 6/60. Retinal detachment involving less than two quadrants consisted of 37.5% (12). A single retinal break was present in 78.1% (25) of cases and 87.5% (28) of the retinal breaks were located in the superotemporal quadrant. The macula was attached in 37.5% (12) of the cases. Sulfurhexafluoride and Perfluoropropane were used in 68.8% (22) and 31.3% (10) respectively. The average follow up period was 1.02 years (range one month to four years). The retina was completely attached in 81.3% (26) of cases at the last follow up. The best corrected distance visual acuity of 6/18-6/60 was found in 40.6% (13) of subjects in the last follow up. There was a transient rise in intraocular pressure in 6.3% (2) of subjects after the procedure. Conclusion: The anatomical success rate following pneumatic retinopexy is quite high (81.3%) with good visual recovery and less morbidity translating to higher productivity for the patient. This procedure, being quicker than the alternatives, will also save surgeon's time making PR a good choice for managing primary rhegmatogenous retinal detachment in countries like Nepal where resources are scarce. Key words: Rhegmatogenous retinal detachment, retinal break, pneumatic retinopexy, Nepal doi: 10.3126/kumj.v6i4.1737 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 466-471